The Monetary Appreciation of Paintings - Stein, John Picard (Journal of Political Economy, 1977)
Price indices for pre-World War II paintings are developed from U.S. and U.K. auction prices, assuming that auctioned paintings are sampled from a fixed underlying stock of paintings. The simple form of the capital-asset pricing model is modified to describe durable goods with risky capital appreciation and constant service yield. Estimated parameters for U.S. paintings are β = 0.82 (SE = 0.34), R 2 = .24, service yield = 1.6 percent (SE = 7 percent). To individual collectors, "performance" is positive to the extent that they value the service yield above 1.6 percent. Paintings are "inefficient." Regressions using U.K. data have no significant β coefficients.